Obesidade e sobrepeso em crianças: fatores associados e riscos à saúde - Silveira, Shynara Jovelina Pianezzola (My University, 2020)
Obesity in children and adolescents is becoming common and growing every day with the ease and practicality of obtaining foods rich in fats and preservatives and, at the same time, the lack of physical activity outside the school environment. The objective of this study is to present consequences that obesity and overweight bring to the lives of children and adolescents, both in their social and affective lives. A bibliometric study was carried out in three databases, on the research topic. It was observed that obesity poses serious risks to the health of the individual and complications in joints, which are important for the distribution of load on the human body. The influence of parents on children's food is directly linked to the development of obesity or not, which has become dangerous over the years, both physically and emotionally in the lives of children, and which often goes unnoticed by the eyes of people around them [resumo fornecido pelo autor].
A obesidade em crianças e adolescentes vem se tornando comum e crescendo a cada dia com a facilidade e praticidade de obter alimentos ricos em gorduras e conservantes e, ao mesmo tempo, à falta de atividade física fora do âmbito escolar. O objetivo do presente trabalho é apresentar consequências que a obesidade e o sobrepeso trazem na vida das crianças e adolescentes, tanto em sua vida social como afetiva. Foi realizado um estudo bibliométrico em três bases de dados, acerca do tema da pesquisa. Foi observado que a obesidade traz graves riscos à saúde do indivíduo e complicações em articulações, que são importantes para a distribuição de carga do corpo humano. A influência dos pais na alimentação das crianças está diretamente ligada ao desenvolvimento da obesidade ou não, que se torna perigosa ao longo dos anos, tanto fisicamente quanto emocionalmente na vida das crianças, e que por diversas vezes passa despercebida ao olhar das pessoas em sua volta [resumo fornecido pelo autor].
Keywords: Obesidade em crianças